Quality of Stroke Patient Information Applied in Randomized Controlled Trials—Literature Review - Alegiani, Anna C.; Rahn, Anne C.; Steckelberg, Anke; Thomalla, Götz; Heesen, Christoph; Köpke, Sascha (Frontiers in Neurology, 2020)
Background: Strokes have a huge impact on patients' quality of life. Although there are potentially effective secondary preventions and treatment options for stroke patients, adherence is mostly low. Low disease and treatment-related knowledge and, consequently, a lack of informed decision-making in stroke patients may contribute to this problem. However, stroke patient information did not seem to have relevant effects on patients' knowledge in randomized controlled trials. One contributing factor may be the lack of thoroughly developed patient information materials. Methods: We aimed to evaluate the quality of patient information materials for stroke patients by using randomized controlled trials, applying quality criteria for evidence-based patient information (EBPI). We conducted a literature search (MEDLINE, Embase, CINAHL, PsycINFO, and CENTRAL). To be included in the review, research had to be randomized controlled trials that provided stroke patient information, were published in English, and had knowledge assessed as the primary endpoint. Authors of primary studies were contacted and asked for information materials applied. Results: We screened 15,507 hits and identified 30 eligible studies. Information materials were available for only eight studies. Analyses revealed that all available materials had important shortcomings concerning EBPI quality criteria [concerning, for example, structural information (e.g., reporting conflicts of interest), content information (e.g., reporting sources of information), or comprehensive descriptions of treatment effects and side effects]. Frequently, treatment effects were reported only narratively without providing absolute numbers, values, or frequencies. Conclusion: Quality of materials differed, but none sufficiently fulfilled EBPI quality criteria. Unsatisfactory trial results concerning patient knowledge and patient involvement in decision-making may at least partially be explained by limitations of the provided materials. Future patient information should consider EBPI quality criteria.